Mixed-ligand complexes of gadolinium carboxylates containing unsaturated bonds in plastic scintillators - Velmozhnaya, E.S.; Bedrik, A.I.; Zhmurin, P.N.; Safronov, D.S.; Doroshenko, A.G. (Functional Materials, 2015)
Results are presented on properties of new synthesized Gd-carboxylates with unsaturated bonds. Gd-containing polystyrene oligomer and plastic scintillators based thereon were obtained using these compounds. The chemical structure of the synthesized compounds was characterized by the IR spectroscopy. Thermographic properties of new complexes were investigated. It is shown that thermal stability of the gadolinium complexes significantly increases with introduction of the unsaturated moiety into their structure and reaches at about 300 °C. The solubility of these structures remains practically unchanged with respect to complexes that do not contain unsaturated bonds. The light output of the obtained Gd-loaded material (plastic scintillators) is kept sufficiently high and reaches 78 % with respect to the unloaded sample.